Interpersonal dependency and online gaming addiction - Škařupová, Kateřina; Blinka, Lukas (Journal of behavioral addictions, 2016)
Background and aims The present study explores the relationship between social motivations and addiction to online gaming and if that possible connection can be explained by the personality traits responsible for social functioning. Methods We employ Bernstein's concept of interpersonal dependency to distinguish healthy dependency, dysfunctional detachment, and destructive overdependence, and Charlton and Danforth's conceptualisation of online gaming addiction and high engagement. An online questionnaire was administered to a self-nominated sample of 4,074 online gamers. Two regression models were constructed to separately explain gaming addiction and high engagement using social motivations to play, while controlling for age, gender, and time spent online. Results High scores on subscales measuring dysfunctional detachment and destructive overdependence were positively associated with online gaming addiction, while healthy dependency was negatively correlated with addiction scores. In contrast, the overall role of social motivation was negligible. Discussion People with healthy relationship profiles are less likely to develop problematic patterns of online gaming. High in-game engagement, although sharing some factors with addiction, was only poorly explained by the study variables, suggesting the mutual exclusiveness of addiction and engagement.
Keywords: dospělí; Dependency, Psychological; motivations to play; Female; dítě; návykové chování; závislost (psychologie); Adult; Linear Models; ženské pohlaví; mladý dospělý; longitudinální studie; Adolescent; interpersonální vztahy; Slovakia; online gaming addiction; lidé; high engagement; Behavior, Addictive; lineární modely; Male; Aged; psychiatrické posuzovací škály; Czech Republic; Internet; videohry; motivace; Young Adult; Video Games; interpersonal dependency; Česká republika; lidé středního věku; Child; Slovenská republika; Interpersonal Relations; senioři; mužské pohlaví; internet; Middle Aged; mladiství; Psychiatric Status Rating Scales; Longitudinal Studies; Motivation; Humans